The Influence of Teachers' Digital Literacy and the Use of Technology Media on Students' Ability to Identify Hoaxes in the Digital Era - Simamora, Nadia Natalia; Alrefay, Khaled Ahmed; Qasem, Arwa Ahmed; Lorenzo, Arnold; Kara, Merve Kara (Cahaya Ilmu Cendekia Publisher, 2024)
Purpose of the study: This study aims to examine the influence of teacher digital literacy and the use of media technology on students' ability to identify hoaxes in the digital era. Methodology: A mixed-method approach was employed, combining quantitative analysis using Multiple Linear Regression with Statistical Package for the Social Sciences (SPSS) and qualitative analysis with the Miles and Huberman model through interviews with teachers. The research sample consisted of 50 teachers and 200 students from secondary schools in both urban and rural areas, selected through purposive sampling. The research instrument used a questionnaire and interview guide. Main Findings: The results indicated that both teacher digital literacy and the use of media technology positively influenced students' ability to identify hoaxes. Teachers with higher digital literacy levels were able to effectively use media technology to guide students in critical thinking and information verification. The use of media technology helped students compare information from different sources and better assess its validity. Novelty/Originality of this study: This study contributes to the field by exploring the combined impact of teacher digital literacy and media technology usage on students' ability to recognize and evaluate misinformation, addressing a critical issue in the context of education in the digital age.